Does the minimum wage affect wage inequality? A study for the six largest Latin American economies - Carlo Lombardo; Lucía Ramírez-Leira; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2022)
Minimum wage (MW) policies are widespread in the developing world and yet their effects are still unclear. In this paper we explore the effect of national MW policies in Latin America's six largest economies by exploiting the heterogeneity in the bite of the national minimum wage across local labor markets and over time. We find evidence that the MW has a compression effect on the wage distribution of formal workers. The effect was particularly large during the 2000s, a decade of sustained growth and strong labor markets. In contrast, the effect seems to vanish in the 2010s, a decade of much weaker labor markets. We also find suggestive evidence of a lighthouse effect: the MW seems to have an equalizing effect also on the wage distribution of informal workers.
Keywords: J22; J31; J38; K31; 330; Minimum Wage; Wages; Labor Markets; Inequality; Informality; Latin America